2016
DOI: 10.1177/0194599816645764
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences of Pigmentation in the Human Vestibular Organs

Abstract: There is greater melanin pigmentation within the vestibular system of African Americans than in Caucasians, similar to what has been described in the cochlea. Racial differences in vestibular physiologic function have been observed in the literature and may be explained by differences in melanin pigmentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…Recently, studies have made significant progress assessing the benefits of Scu, which exhibited neuroprotective effects, including anti-oxidant, anti-inflammatory and anti-apoptotic activities in numerous diseases (12–14). Additionally, previous studies demonstrated the beneficial effects of Scu in vascular endothelial dysfunction (15,16), myocardial infarction (17), colorectal cancer (18,19) and other types of cancer (20,21). Scutellarein (5,6,7,4′-tetrahydroxy flavone; Scue) is the hydrolyzed product of Scu in perennial herbs, including Scutellaria baicalensis, Scutellaria lateriflora and Scutellaria barbata (22,23).…”
Section: Introductionmentioning
confidence: 90%
“…Recently, studies have made significant progress assessing the benefits of Scu, which exhibited neuroprotective effects, including anti-oxidant, anti-inflammatory and anti-apoptotic activities in numerous diseases (12–14). Additionally, previous studies demonstrated the beneficial effects of Scu in vascular endothelial dysfunction (15,16), myocardial infarction (17), colorectal cancer (18,19) and other types of cancer (20,21). Scutellarein (5,6,7,4′-tetrahydroxy flavone; Scue) is the hydrolyzed product of Scu in perennial herbs, including Scutellaria baicalensis, Scutellaria lateriflora and Scutellaria barbata (22,23).…”
Section: Introductionmentioning
confidence: 90%
“…Specimens from adults that had available audiometric data were selected for analysis. The adult temporal bones studied were the same as those used in previous studies from our institution (Sun et al, 2014;Erbele et al, 2016). The pediatric temporal bones analyzed were from the same collection.…”
Section: Human Temporal Bone Subjects and Imagingmentioning
confidence: 99%
“…Pigmentary disorders have similarly been associated with congenital deafness in dogs and cats (Strain, 2004(Strain, , 2017. Conversely, differential levels of pigmentation have been hypothesized to alter susceptibility to noise-induced hearing loss and presbycusis (Bunch and Raiford, 1930;Ardiç et al, 1998;Ishii and Talbott, 1998;Murillo-Cuesta et al, 2010;Lin et al, 2011Lin et al, , 2012Sun et al, 2014), and potentially vestibular dysfunction (Erbele et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have supported the theory that vestibular anatomy and dysfunction may have differing phenotypes based on race; 7,14,15 however, this concept is poorly understood and little studied. Erbele et al noted that there is a significant increase in melanin pigmentation in the inner ear of African Americans compared with Caucasians, similar to prior cochlear findings.…”
mentioning
confidence: 99%